Carcass and Meat Quality Characteristics of Wild Boar Crossbreds - Neena Amatya Gorkhali; Prashanna Koirala; Saroj Sapkota; Achyut Mishra; Ujjwol Subedi; Deepak Adhikari; Bhoj Raj Pokhrel; Nirajan Bhattarai (Indonesian Journal of Applied Research (IJAR), 2021)
Due to the growing interest in the production and consumption of wild boar meat, the quality attributes of meat products should be well established. To characterize the quality of wild boar cross meat, two males and two females reared in the same environment were slaughtered at an average of one year of age, and meat samples were was collected and analyzed for different parameters such as for moisture, pH value, protein, fat, iron, phosphorous, calcium, water holding capacity through the measure of cooking loss. Data obtained for live body weight, carcass biochemical characteristics, and meat quality traits were submitted to one-way analysis of variance (ANOVA) using a general linear model (uni-variate) in Statistical Package for Social Sciences (SPSS) computer program and the level of significance was determined observing the probability value (p) obtained through ANOVA of respective traits. To study the association among nutritive values and body parts, Pearson’s correlation coefficients were determined using in Statistical Package for Social Sciences (SPSS) computer program. The pH values were found to be in the range of 5.78 to 5.90. Moisture, total ash, fat, and protein contents were observed to be in the range of 71.38 to 73.57 %, 0.89 to 1.10 %, 4.34 to 5.54 %, and 16.73 to 18.84 % respectively. Iron, phosphorous, and calcium content were found to be in the range of 1.94 to 2.94 mg/100g, 20.17 to 37.57 mg/100g, and 170.68 to 190.88 mg/100g respectively whereas cooking loss was in the range of 31.59 to 26.88 %. Sensory evaluation of meat samples was examined by a group of panelists according to the hedonic rating test. The consumer preference was similar to both types of meat samples (male and female). The overall acceptance; however, were higher in female samples than in male samples due to boar taint evident during the cooking or eating of pork derived from non-castrated male pigs once they reach puberty. The comparison of wild crosses among available commercial pigs and indigenous pigs is warranted for further studies with an appropriate and defined production system to obtain lean meat as per the consumer preferences which could be extensively used in commercial pig production to provide high-quality pork.